Diseño Conceptual de una Planta de Extracción de Saponinas Presentes en el Jugo de Fique - Vélez Salazar, Yesid Hernán; Velásquez Flórez, Mario Alonso (Ingeniería, 2020)
Context: Saponins belong to a group of molecules with industrial applications, particularly in the food industry as a foam stabilizer in soft drinks. During 2013 to 2017, its market increased about 50%, becoming an important economic sector that has promoted a strong interest in the optimization of different extraction processes from different natural sources. Method: A technological surveillance report was made evaluating the applicability, extraction and economic aspects of saponins worldwide. The conceptual design of a pilot plant for the extraction of saponins from fique’s juice was carried out based on the results obtained from the analysis of a decision matrix. Results: A viable alternative for the extraction of saponins from fique’s juice is flocculation, which advantages lie on its technological simplicity, low energy consumption, direct applicability to the matrix of interest and use of solvents such as water and ethanol. Conclusions: Using Aluminum Polychloride (PAC) as a flocculant, due to its ability to remove organic matter and its selectivity, saponins are recovered in the clarification. The conceptual design presents a pilot plant with a capacity of 67.462 L/h and an efficiency of 87,45%.